Die Schweizerhütte – a Moniuszko World Premiere Delayed for Almost Two Hundred Years: Questions, Hypotheses and New Prospects for Research - Zieziula, Grzegorz (Interdisciplinary Studies in Musicology, 2025)
In autumn 2011, during research conducted at the Library, Museum and Archives of the Warsaw Music Society, I identified an unknown early work by Stanisław Moniuszko entitled Die Schweizerhütte (c.1839–1840). It is a two-act German-language komische Oper, which, on the list of his early works, is most likely the missing link from the time of his studies with Carl Friedrich Rungenhagen in Berlin. Preserved only in the form of a vocal score, the opera was probably also completed in a full orchestral score. In a new orchestration, the work received its premiere 180 years late, on 16 November 2018, at the Warsaw Chamber Opera, where it was performed several more times, and on 21 August 2019 the same production was also shown in Kudowa-Zdrój during the 57th International Moniuszko Festival. Moniuszko based the German text of Die Schweizerhütte on the libretto of Carl Blum’s comic opera Mary, Max und Michel (from 1836), but shortened or omitted some passages, added different stage directions and inserted textual interpolations of unknown authorship. In my discussion, I focus on surveying the score and presenting the musical setting in relation to the plot. I particularly emphasise the thematic connection between the overture and the finales of both acts, as well as the consistent use of reminiscence motifs. I identify musical quotations from Étienne Nicolas Méhul and Michael Haydn, as well as one self-quotation (from the String Quartet No. 1). I also mention the ‘afterlife’ of certain musical numbers in well-known operas by Moniuszko. Paradoxically, it is precisely this German-language work by the barely twenty-year-old Moniuszko that demonstrates his surprisingly mature reflections on the internal integration of a work and awareness of the musical-dramaturgical rules governing the opera genre. Although on returning from Berlin he did not find favourable conditions for further development, these experiences had a significant influence on his style, which combined local tradition with the poetics of European opera, primarily Italian (Gioachino Rossini) and French (Daniel Auber, Adolphe Adam), but also – through the inclusion of solo number in the form of Lied – German (Carl Maria von Weber).